Antioxidants and immune response and infectious diseases - Meydani, Simin (Henry Stewart Talks, 2007)
Essential antioxidants, Antioxidant defenses in immune infection, Antioxidants-host defense-infection: a complex interaction, Vitamin E deficiency, CVB3, Effect of host age, Effect of virus origin, Effect of passage, Antioxidant supplementation, Vitamin E and immune response in the aged, Not all antioxidants behave the same, Clinical benefits from antioxidant supplementation, Zinc supplementation, Selenium, How do antioxidants exert their effect?, T-cell function
Archived at 2018/05/31